2010
DOI: 10.19030/iber.v9i1.515
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions On Water Reuse Options: The Case Of Sulaibiya Wastewater Treatment Plant In Kuwait

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…In Kuwait, where recycled water availability is already common, the majority of inhabitants do drink both tap and bottled water. However, the majority would not want to use recycled water for drinking when explicitly asked [9]. In our study, hypothetical technologically recycled drinking water made from wastewater found its highest acceptance in activities not involving oral consumption of water, such as watering the garden or pot plants, toilet flushing, or car washing; other non-consumption activities would probably be rated likewise.…”
Section: Relevance Of Reuse and Estimation Of Acceptable Usagementioning
confidence: 67%
See 4 more Smart Citations
“…In Kuwait, where recycled water availability is already common, the majority of inhabitants do drink both tap and bottled water. However, the majority would not want to use recycled water for drinking when explicitly asked [9]. In our study, hypothetical technologically recycled drinking water made from wastewater found its highest acceptance in activities not involving oral consumption of water, such as watering the garden or pot plants, toilet flushing, or car washing; other non-consumption activities would probably be rated likewise.…”
Section: Relevance Of Reuse and Estimation Of Acceptable Usagementioning
confidence: 67%
“…New technologies may help to provide drinking water without needing to permanently take raw water from natural resources, and may also help increase raw water availability and quality of raw water resources. The further treatment of wastewater after its treatment in a sewage plant is already an important issue in several EU and non-EU countries, where water shortages are common [1,9,10]. Sewage plant outputs are then cleaned further for fit-for-purpose requirements, like agricultural applications, industrial needs, or even drinking purposes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations